Генерал в Белом доме - Иванов Роберт Федорович (Тайны XX века, 2000)
Экземпляры: КХ (20060510) / Инвентарный номер: 1056732 / Цена: 45.00 / Сис.шифр: 63.3(7) / Авт.знак: И 20 / ГРНТИ: 03 / ББК: 63.3(7Сое)6